Investigations on cold spray tungsten/tantalum coatings for plasma facing applications. (March 2023) - Neu, R.; Maier, H.; Böswirth, B.; Elgeti, S.; Greuner, H.; Hunger, K.; Kondas, J.; von Müller, A.
Highlights: W/Ta coatings on steel with 2 mm thickness were produced by cold spray. The maximum W fraction in the coating was 70% and the porosity was smaller than 1%. No defects occurred in high heat flux tests at power loads up to 4 MW/m 2 . Abstract: Cold gas spraying for the production of thick tungsten (W) coatings has been investigated for use at plasma facing components in fusion devices. Since the brittle nature of W strongly impedes its deposition, a systematic study was performed using mixtures of tungsten and tantalum (Ta) powders. Whereas the use of 100% W powder was not successful yet, 2 mm thick coatings on steel were produced by using a W/Ta powder mixture with 90 vol% W, yielding a W content in the coating of 70 vol%. The coatings show negligible porosity and very good adhesion to the substrate. High heat flux experiments on samples with the size 80 × 80 mm 2 were performed in order to investigate the behaviour under low (≤4 MW/m 2 ) steady state loads and high power (∼40 MW/m 2 ) transients. During the pulses with low power density, being typical for applications at the main chamber first wall, no defects were observed and a thermal conductivity close to that of the bulk materials was found. During the high power transients lasting for 200 ms cracks parallel to the surface appeared inside the coating.